2007
DOI: 10.1016/j.jtcvs.2007.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic obstructive pulmonary disease on postoperative lung function and complications in patients undergoing operations for primary non–small cell lung cancer

Abstract: Because the pattern of lung function change is different in patients with chronic obstructive pulmonary disease compared with that of patients with normal lung function, surgery can be offered to carefully selected patients with lung cancer, even in the presence of severely limited lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
(23 reference statements)
2
18
1
2
Order By: Relevance
“…to maintain adequate flow at low lung volumes. This is in line with our previous report on 35 COPD patients in whom 18% and 25.6% improvement in FEF50 was registered after lobectomy, compared with slight decrease of these values in the control group [25]. The tendency of smaller FEV1 loss in patients with moderate and severe COPD, compared with patients with better preserved lung function, as registered in our study, additionally supports similar results published in recent years, demonstrating that such a finding does not always exist only due to lung volume reduction effect [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…to maintain adequate flow at low lung volumes. This is in line with our previous report on 35 COPD patients in whom 18% and 25.6% improvement in FEF50 was registered after lobectomy, compared with slight decrease of these values in the control group [25]. The tendency of smaller FEV1 loss in patients with moderate and severe COPD, compared with patients with better preserved lung function, as registered in our study, additionally supports similar results published in recent years, demonstrating that such a finding does not always exist only due to lung volume reduction effect [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have shown minimal loss or even improvement of pulmonary function after lobectomy by the so-called "lung volume reduction effect" in patients with airflow limitations, thus making estimations of postoperative pulmonary function difficult. 24) Quality of life after lobectomy in patients with COPD is similar to patients without COPD, despite an increased risk of postoperative cardiopulmonary complications, 25) and there were no in-hospital deaths in the current study.…”
Section: Discussionmentioning
confidence: 53%
“…Acceptable peri-operative mortality rate (0-6%) with prolonged cancer-free interval and sustained functional improvement (up to 1 yr) have been reported in selected patients with pre-operative FEV1 ,60% [49,212,219,223,225]. Although long-term survival after lobar LVRS for stage I lung cancer is limited by physiological rather than oncological factors, outcomes are still better than those reported for any other modality of treatment.…”
Section: Surgical Techniques In Lung Cancermentioning
confidence: 99%